The influence of social affiliation on individual vocal signatures of northern resident killer whales ( Orcinus orca ) - Nousek, A. E.; Slater, Peter James Bramwell; Wang, C.; Miller, Patrick (Biology Letters, 2006)
Northern resident killer whales ( Orcinus orca) live in highly stable groups and use group-specific vocal signals, but individual variation in calls has not been described previously. A towed beam-forming array was used to ascribe stereotyped pulsed calls with two independently modulated frequency contours to visually identified individual killer whales in Johnstone Strait, British Columbia. Overall, call similarity determined using neural networks differed significantly between different affiliation levels for both frequency components of all the call types analysed. This method distinguished calls from individuals within the same matriline better than different calls produced by a single individual and than chance. The calls of individuals from different matrilines were more distinctive than those within the same matriline, confirming previous studies based on group recordings. These results show that frequency contours of stereotyped calls differ among the individuals that are constantly associated with each other and use group-specific vocalizations, though across-group differences were substantially more pronounced.